Akirin1 promotes myoblast differentiation by modulating multiple myoblast differentiation factors. Issue 3 (1st March 2019) - Sun, Wenqiang; Hu, Shenqiang; Hu, Jiwei; Qiu, Jiamin; Yang, Shuang; Hu, Bo; Gan, Xiang; Liu, Hehe; Li, Liang; Wang, Jiwen
Abstract : Akirin1 is found to be involved in myoblast differentiation. However, the mechanism by which the Akirin1 gene regulates myoblast differentiation still remains unclear. In the present study, we found that ectopic expression of Akirin1 promoted myoblast differentiation by increasing the expression of myogenic regulatory factor (MRF) 4 ( MRF4 ) and myocyte enhancer factor 2B ( MEF2B ) mRNA. Additionally, we showed that ectopic Akirin1 induced cell cycle arrest by up-regulating p21 mRNA. To further uncover the mechanism by which Akirin1 promotes myoblast differentiation, we showed that the enhanced Akirin1 increased the mRNA expression of P38α. Importantly, the enhanced MRF4 expression by Akirin1 can be abrogated by treatment of SB203580, a p38 inhibitor. Similarly, we found that enhanced MEF2B expression by Akirin1 can be abrogated by treatment with LY294002, a PI3K inhibitor. Together, our results indicate that Akirin1 promotes myoblast differentiation by acting on the p38 and PI3K pathways and subsequently inducing the expression of myoblast differentiation factors.